Bills on The Model Relations with Central Government Money in The Bank Indonesia Circulating January 1999 – December 2001 - Zubaidah Zubaidah (Jurnal Ilmiah ESAI, 2010)
The number of bills, especially the Central Government Debt, is one of the obligations and responsibilities that must be paid, because it determines the level of development within a country, on the basis of the amount owed. During this time, especially 1999 - 2001, changes in money supply has fluctuated quite large, so it needs to be examined the causes of the most likely to influence it, in order to understand and predict future behavior.  One of the reasons Bill on Central Government Money Supply Changes chosen because it is a causative factor that has proved to have the strongest correlation on the theory of the previous observations made among the various other factors during that period. Change Money Supply with the factor charges at the central government as one of the reasons that influence it, have a very strong correlation between other factors such as the theoretical and logical thought to significantly affect the Money Supply Changes. This research will seek to develop a relationship model of the Money Supply Changes due to charges at the experimental Pemerinyah Center regression models 48 to test the most likely to produce the best model, based on the similarity or closeness relation both linear and non linear (the highest correlation between the estimated results with actual data ) which actually has happened in reality.  In general it can be concluded that the Normal Linear Model can be used to explain the causal relationship that correlates highly correlated +0.04 or negative. But specifically concluded Square Inverse Lag-1 can be even better if used to explain the causal relationship of correlation to correlate 0.1 or higher. (highest). So the bill on the relationship with the Center Pemerinyah Money Supply Changes over the study period 1999 - 2001, according to observations with the best model is: Money Supply (in trillions) 228 billion in the previous period of the Central Government. Keywords :  charge on the central government with the money supply in the banking Indonesia.